Enhancing Gingival Esthetics by Depigmentation - Shrestha, Rejina; Pradhan, Shaili (Nepal Journal of Health Sciences, 2022)
The color of the gingiva has an important role in determining the esthetics of an individual. There are many etiological factors responsible for gingival pigmentation. Depigmentation of the gingiva can be done by various procedures which include scalpel surgery, cryosurgery, bur abrasion, laser surgery and electrosurgery. Among these procedures, laser depigmentation is the most comfortable method.